2022
DOI: 10.1017/s1366728921001097
|View full text |Cite
|
Sign up to set email alerts
|

Planning ahead: Interpreters predict source language in consecutive interpreting

Abstract: Interpreters are hypothesized to anticipate the source language (SL) in comprehension and the target language (TL) in production to facilitate timely delivery. In two experiments, we examined whether interpreters make more predictions in SL comprehension in consecutive interpreting than in regular language comprehension and whether such enhanced prediction (if any) is constrained by cognitive resources. Participants were quicker at reading a predictable versus unpredictable critical word and/or following words… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
(108 reference statements)
1
5
1
Order By: Relevance
“…Our findings regarding the effects of working memory align with previous findings about its influence on interpreting performance [ 22 , 34 , 35 , 46 , 63 , 75 ]. Moreover, our data suggests that, akin to language proficiency, working memory in comprehension restricts the conceptual understanding of the source language.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings regarding the effects of working memory align with previous findings about its influence on interpreting performance [ 22 , 34 , 35 , 46 , 63 , 75 ]. Moreover, our data suggests that, akin to language proficiency, working memory in comprehension restricts the conceptual understanding of the source language.…”
Section: Discussionsupporting
confidence: 91%
“…Working memory has long been assumed to underlie interpreting performance [see 45 , for a review]. Zhao et al [ 22 ] showed that interpreters make lexical predictions in source language comprehension, but not when their working memory resources are depleted. Christoffels, de Groot, and Kroll [ 46 ] showed that trained interpreters outperformed both bilingual students and English teachers in working memory but not necessarily language proficiency, thus suggesting that professional interpreting practice is particularly associated with better (verbal) working memory capacity.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing interpreters' prediction while reading for comprehension and reading to interpret in the consecutive mode, prediction effects are stronger when the interpreters need to interpret, although enhanced prediction disappears when the cognitive load is high. These results indicate that interpreting increases prediction experience both during comprehension (in the source language) and production (in the target language) (Zhao et al, 2022).…”
Section: Prediction and Interpretersmentioning
confidence: 70%
“…Thus, listening for the purpose of consecutive interpreting may be more likely to involve phonological prediction than listening for the purpose of comprehension. Zhao, Chen, and Cai [ 58 ] found that bilinguals read predictable but not unpredictable words faster in their L2 when they were reading to consecutively interpret rather than to recall. This suggests that prediction might be enhanced during comprehension when interpreting consecutively.…”
Section: Introductionmentioning
confidence: 99%
“…We also hypothesized that a consecutive interpreting task would lead to earlier and more predictive fixations on images representing predictable words, and may lead to predictive fixations on phonological competitors after fixations on these predictable images. Consecutive interpreting requires focused attention and this might both improve speech recognition in noise [ 7 ] and encourage earlier or greater prediction [ 48 , 58 ]. In addition, consecutive interpreting engages the production mechanism, and this might lead to word-form prediction [ 1 ].…”
Section: Introductionmentioning
confidence: 99%